RatDNA: DATABASE ON MICROARRAY STUDIES OF RATS BEARING GENES ASSOCIATED WITH AGE-RELATED DISEASES - O. S. Kozhevnikova; M. K. Martyschenko; M. A. Genaev; E. E. Korbolina; N. A. Muraleva; N. G. Kolosova; Y. L. Orlov (Вавиловский журнал генетики и селекции)
The purpose of the RatDNA database is the development of experimental methods for basic molecular studies of human age-related diseases in rats involving microarray tests of gene expression. Despite the obvious correlation between life expectancy and heredity and numerous biomedical studies on aging, little is known about genetic factors determining aging processes. People do not die of «healthy» aging: at any age conditions whose probability increases with age become the cause of their death. Age-related macular degeneration (AMD) becomes the main cause of vision problems and sight loss in people aged above 50. Structural and functional changes in the retina characteristic of aging are similar to those observed at early stages of AMD. They underlie the pathogenesis of this disease, but not always lead to its development. RatDNA database contains information on genes associated with age-related diseases, in particular AMD, and experimental data about their expression in tissues of a model rat strain. The database is available at http://pixie.bionet.nsc.ru/ratdna/rat/index.php.